MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPA MENGGUNAKAN METODE INKUIRI TERBIMBING PADA SISWA KELAS VI SDN 3 LABUHAN DALAM BANDAR LAMPUNG - Siti Sarah (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
Based on observations and experiences during teaching at SD Negreri 3 Labuhan Dalam, it is known that the average score of grade VI student examinations conducted in the even semester of science subjects is low, namely 54. This score indicates that student learning outcomes are low and have not reached the Minimum Completeness Criteria. (KKM), namely 60. The learning carried out so far is still conventional. This is due to the limitations of teachers in applying the learning model. Based on the problem, one of the learning models that are thought to be able to overcome this problem is learning using a guided inquiry model. In inquiry learning, students are more directly involved during the learning process to solve problems given by the teacher. This classroom action research was conducted in 3 cycles. The factors observed were student activity and learning outcomes. The research objective was to describe the increase in activity and student learning outcomes after guided inquiry learning. Based on the research results, it is known that guided inquiry learning can improve student activity and learning outcomes from cycle to cycle. There is an increase in student learning activities in each cycle. In the first cycle the student learning activity was 1.80 in the category of "moderate activity", in the second cycle it increased from 0.22 to 2.02 in the "moderate activity" category, and in the third cycle the student activity increased again by 0.19 to 2, 21 with the category "Medium Activity". Student learning outcomes in each cycle. In the first cycle the average student learning outcomes was 58.84 in the "Not Complete" category, then in the second cycle it increased by 2.41 to 61.25 in the "Completed" category, and in the third cycle the average learning outcomes increased again. amounted to 6.88 to 68.13 with the category "Completed".